Exploring Primary School Teachers’ Intention to Use E-Learning Tools during the COVID-19 Pandemic - Marina Aivazidi; Christos Michalakelis (Education Sciences, 2021)
It is commonly accepted that the COVID-19 pandemic has had a crucial effect on many aspects of people’s lives. The limitations placed on human relations have also affected education. The mandatory implementation of e-learning and the use of the information and communication technology tools in the teaching process have been the most important changes at all educational levels. However, the teaching staff plays a key role in every educational change. In this study, we examined the intention of elementary school teachers to use an e-learning platform. Our findings are consistent with those of previous studies, which have found that teaching skills, teachers’ beliefs, and the appropriate infrastructure are all critical factors for the successful implementation of information technology in the educational process.